Randomized prenatal and postnatal nutrient supplementation shows no long-term impact on cortical gray matter in Ghanaian children - Ayete Labi, Fatimah B.; Midrigan-Ciochina, Ludmila; Prado, Elizabeth L.; Adu-Afarwuah, Seth; Dewey, Kathryn G.; Arnold, Charles D.; Manu, Adom; Angmorterh, Seth Kwadjo; Arko-Mensah, John; Mensah, Mavis Osipi; Nti, Helena; Aryee, Lois M. Donkor; et al. (Frontiers in Human Neuroscience, 2026)
IntroductionMaternal and child undernutrition are linked to atypical brain development in children. Provision of pre- and post-natal small-quantity lipid-based nutrient supplements (SQ-LNS) has been shown to positively impact children’s growth and development. It is unknown, however, whether SQ-LNS affects child brain morphology.MethodsThe present study used data from the International Lipid-based Nutrient Supplements randomized controlled trial in Ghana. Participants were 231 children (Mage = 10.6 years; 49.4% female) exposed to maternal iron and folic acid supplements prenatally (n = 113, control group) or maternal SQ-LNS prenatally until 6 mo postpartum and child SQ-LNS from age 6 to 18 months (n = 118, SQ-LNS group). Children underwent magnetic resonance imaging (MRI) of brain anatomy. Primary outcomes were total gray matter volume, cortical gray matter thickness, and cortical gray matter volume assessed with whole-brain analyses. Secondary outcomes were thickness and volume of a priori specified cortical and subcortical regions assessed with region-of-interest (ROI) analyses. Basic and full covariate models were tested and corrected for multiple comparisons.ResultsWhole-brain analyses revealed no significant differences between groups in total gray matter volume or cortical gray matter thickness or volume. Cortical ROI analyses showed the SQ-LNS versus control group had greater right caudal anterior cingulate cortex (ACC) thickness [mean (95%CI): 2.78 (2.73, 2.84) vs. 2.72 (2.67, 2.77); effect size = 0.21] and reduced left rostral ACC volume [2575.1 (2477.3, 2672.8) vs. 2678.74 (2568.7, 2788.8); effect size = 0.18]. Subcortical ROI analyses showed the SQ-LNS versus control group had greater volume of the left pallidus [1794.45 (1759.10, 1829.80) vs. 1726.13 (1685.05, 1767.21); effect size = 0.33] and right nucleus accumbens [751.54 (729.83, 773.24) vs. 705.73 (684.21, 727.24); effect size = 0.39]. Significant group differences did not hold after correction for multiple comparisons.DiscussionIn this cohort, pre- and post-natal SQ-LNS supplementation did not significantly alter total or cortical gray matter thickness and volume at 10 years, though secondary ROI analyses indicated subtle, non-robust differences in selected regions.